2020
DOI: 10.1021/acs.joc.0c01906
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Mechanism, Origin of Stereoselectivity, and Ligand-Dependent Reactivity in the Pd(II)-Catalyzed Unbiased Methylene C(sp3)–H Alkenylation–Aza-Wacker Cyclization Reaction

Abstract: The mechanism, origin of stereoselectivity, and ligand-dependent reactivity of Pd(II)-catalyzed methylene C(sp 3 )−H alkenylation−aza−Wacker cyclization to form (E)-β-stereogenic γ-lactam have been comprehensively studied by density functional theory (DFT) calculations. The calculated results reveal that the methylene C−H activation assisted by K 2 CO 3 via the concerted metalation− deprotonation mechanism is found to be the most preferred pathway, where the enantioselectivity is distinguished by the orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Guo, Li et al . also explored the mechanism of the above transformation [38] . Their DFT calculation revealed that a concerted metalation−deprotonation mechanism assisted by K 2 CO 3 was the most preferred pathway determining rate and enantioselectivity.…”
Section: Formation Of Monocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo, Li et al . also explored the mechanism of the above transformation [38] . Their DFT calculation revealed that a concerted metalation−deprotonation mechanism assisted by K 2 CO 3 was the most preferred pathway determining rate and enantioselectivity.…”
Section: Formation Of Monocyclesmentioning
confidence: 99%
“…[37] Guo, Li et al also explored the mechanism of the above transformation. [38] Their DFT calculation revealed that a concerted metalation À deprotonation mechanism assisted by K 2 CO 3 was the most preferred pathway determining rate and enantioselectivity. According to their results, enantioselectivity arose from the relative orientation of the substrate methyl group and the phenyl group of the chiral ligand.…”
Section: Intermolecular Ring Formationsmentioning
confidence: 99%
“…Interestingly, most of these rely on the formation of metal nitrenoids in the form of metal imido or nitrene intermediates to achieve the activation process . On the other hand, transition metal activation followed by nitrogen addition and Wacker-type oxidative processes have also received significant attention . Moreover, metal-free methods involving formal C–H functionalization have also been studied (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“… 5 On the other hand, transition metal activation followed by nitrogen addition and Wacker-type oxidative processes have also received significant attention. 6 Moreover, metal-free methods involving formal C–H functionalization have also been studied ( Figure 1 ). 7 These reactions have become ubiquitous in organic chemistry to the extent of being extensively used in late-stage functionalization of complex molecules and in many total syntheses.…”
Section: Introductionmentioning
confidence: 99%